Implementation of a geographical routing scheme for low Earth orbiting satellite constellations using intersatellite links. (26th June 2020) - Roth, Manuel; Brandt, Hartmut; Bischl, Hermann
Summary: A major problem for low Earth orbit (LEO) constellations with intersatellite links is the efficient routing of the data packets through such a highly dynamic network. In order to achieve a worldwide coverage even in remote areas and Internet access with a limited amount of gateway stations, intersatellite links are a promising approach. Since LEO constellations represent a distinct, highly dynamic routing environment, specific strategies are needed. To this end, a suitable geographical routing scheme is proposed and investigated in two Walker Star constellations. The proposed scheme targets reliable transmissions with low latency and high data rates. The approach is based on a geographical address identifier in Layer 2 of the communication stack. The globe is thus divided into geographical areas that determine this identifier in the MAC address of the terminals. As mobile terminals are considered, the MAC addressing scheme is flexible, whereas the IP addresses of the terminals remain static. This decoupling allows for flexibility in the choice of the address resolution scheme. Moreover, the geographical identifier in the MAC address enables fast routing table lookups and switching. The proposed routing scheme also takes possible overloads of the satellites due to traffic into account and applies a rerouting procedure. When a packet arrives in the geographical area of the destination terminal, a local rerouting scheme is applied if needed. The proposed approaches take handover events that possibly occur during a transmission into account. Furthermore, the scan angles of the satellites have been adapted to the constellations to provide full coverage and high elevation angles. So a robust and adaptable routing scheme is provided for a dynamic environment where satellites and terminals are constantly moving. The proposed definitions and procedures have been implemented in a system level simulator, which allows for comparisons with adjustable parameters in various scenarios. In this work, an Iridium‐like constellation and a megaconstellation are investigated and compared regarding the address resolution procedures, the average end‐to‐end transmission delay, and the dropping and rerouting rates. Additionally, the signaling overhead is compared with other approaches. The simulator and results of the simulations provide grounds for further research w.r.t. the routing in satellite constellations using intersatellite links. Abstract : A geographical routing scheme for LEO satellite constellations with intersatellite links is proposed, implemented, and analyzed for two Walker Star constellations. The approach targets reliable transmissions with low latency and high data rates even in scenarios with significant traffic load. An Iridium‐like constellation and a megaconstellation are investigated and compared regarding the address resolution procedures, the average end‐to‐end transmission delay, and the dropping and rerouting rates using a system level simulator.